KAJIAN EKSPERIMENTAL STRESSED SKIN PANEL MENGGUNAKAN CROSS-LAMINATED TIMBER DAN GLULAM - Naomi Pratiwi; Johannes Adhijoso Tjondro; Alexander Mario Kwa (CRANE: Civil Engineering Research Journal, 2026)
Engineered wood products such as glulam and Cross-Laminated Timber (CLT) offer sustainable alternatives to large-dimension structural timber. This study investigates the flexural behavior of Stress Skin Panels (SSP) composed of CLT skins and glulam stringers, comparing single-skin (SSP-T) and double-skin (SSP-G) configurations using Sengon wood. Static bending tests were conducted on two specimens per configuration to evaluate strength, stiffness, ductility, and failure modes. Results show that the double-skin configuration yields limited increases in ultimate capacity by 7.8% and stiffness by 8.2%, indicating partial composite action. However, deformation capacity increases significantly by 71.2%, with a 38% improvement in ductility ratio and a 61.5% reduction in bending stress, reflecting more uniform stress distribution. Single-skin panels exhibit brittle stringer failure, whereas double-skin panels demonstrate progressive failure governed by interfacial slip and delamination. These findings highlight the effectiveness of double-skin SSP in enhancing ductility and post-elastic performance.